An Inquiry into the Effect of Blended Learning and Learning Styles on English Learning Outcomes - Rochmahwati, Pryla; Rukminingsih, Rukminingsih (Journal of English Language, Literature, and Teaching (J-ELLiT), 2017)
This present research applied mixed methods research. The design of the research was sequential design. Population in this research was 94 students of the 6th semester of English Department in the State College for Islamic Studies (STAIN) Ponorogo. Since it applied population sampling technique, the number of sample was the same as the number of population. The researcher employed questionnaires, documentation, observation and in-depth interview as data collection technique. Since the hypothesis is intended to find the effect of studentsâ learning styles and their perception of blended learning on learning outcomes, the Simple Linier Regression by using SPSS 19.00 for Windows was applied. The second phase, the result of observation and in-depth interview were analyzed by Miles and Hubermanâs view of qualitative data analysis consisting of data reduction, data display, and drawing conclusion. The findings showed that there is a significant effect of studentsâ learning style and their perception of blended learning on learning outcomes and the equation regression is Y = 76.784 + 0.595X1 + 0.312X. During the implementation, the lecturer adapted various models of blended learning for boosting studentsâ learning outcomes. Lecturer mixes the use of online and offline interaction in the teaching and learning process. It relates to the concept of Blended learning which integrate face-to-face and virtual learning environment. Students are given opportunity to convey their idea online through Edmodo platform, email and blog as well as communicating and discussing particular issues by face-to-face interaction with their classmates and lecturer.Â